Revision of the genus Ommatoiulus Latzel, 1884 (Julida, Diplopoda) in Portugal, with description of six new species - Akkari, Nesrine; Enghoff, Henrik (European Journal of Taxonomy, 2017)
In this work we present a revision of the genus Ommatoiulus Latzel, 1884 in Portugal. Based on recently collected material and older museum samples, including type specimens, we describe six new species to science, viz. Ommatoiulus alacygni sp. nov., O. camurus sp. nov., O. denticulatus sp. nov., O. litoralis sp. nov., O. staglae sp. nov. and O. stellaris sp. nov. The species O. alacygni sp. nov., O. denticulatus sp. nov. and O. staglae sp. nov. described from the Algarve are outstanding by their extremely reduced mesomerital process. The species O. porathi (Verhoeff, 1893) and O. andalusius (Attems, 1927) are recorded and redescribed for the first time after their original description. The finding of O. andalusius – originally described from Andalusia in Spain – constitutes a new record for Portugal together with two species, viz. O. fuentei (Brolemann, 1920) and O. martensi Mauriès, 1969. The taxonomic status of several species is revised. Thus Archiulus (Schistocoxitus) cingulatus Attems, 1927 is here considered as a junior synonym of Ommatoiulus lusitanus (Verhoeff, 1895) while Schizophyllum cervinum Verhoeff, 1910 is synonymized with Ommatoiulus moreleti (Lucas, 1860). An identification key to all hitherto known Portuguese species of Ommatoiulus is presented as well as a distribution map illustrating the various species occurrences in the country.